Identifikasi Bakteri Escherichia Coli Pada Air Kolam Renang Umum di Politeknik Negeri Ambon - M Fadly Kaliky; Rahma Tunny (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Swimming pool water is water used for sports and its quality meets health requirements. To find out the number of Escherichia coli bacteria identified in the adult public swimming pool water at the Ambon State Polytechnic. This type of research is descriptive research located at the Ambon State Polytechnic. The population in this study is swimming pool water and the samples taken were 2 samples from an adult swimming pool and 2 samples from a children's swimming pool. The research results showed that the results of examination of 3 swimming pool water samples did not contain Escherichia coli bacteria and 1 swimming pool water sample contained Escherichia coli bacteria, and for Coliform bacteria there were 2 positive samples and 2 negative samples containing Coliform bacteria. Based on the results of research conducted at the Ambon Class II BTKL PP Biology Laboratory, it can be concluded that of the 4 swimming pool water samples taken from public swimming pool water at the Ambon State Polytechnic, there were 3 negative samples and 1 positive sample containing Escherichia coli bacteria, and for bacteria There were 2 positive samples for coliform and 2 negative samples containing coliform bacteria